2021
DOI: 10.2217/fon-2021-1072
|View full text |Cite
|
Sign up to set email alerts
|

Daratumumab Utilization and Cost Analysis among Patients with Multiple Myeloma in a US Community Oncology Setting

Abstract: Background: The introduction of daratumumab into the treatment of multiple myeloma has improved outcomes in patients; however, community oncologists often dose more frequently than the US FDA-approved label. Materials and methods: Integra analyzed its database to elucidate daratumumab treatment patterns and the impact of increased utilization on the cost of care for multiple myeloma. Results: Following week 24, 671 (65%) of 1037 patients remained on daratumumab-containing regimens, with 330 patients continuing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The analysis did not consider patient attrition over time, possibly leading to an overestimate in adherence. 7 However, we show that duration of therapy for DARA-based regimens in the real-world is relatively long and adherence is high. Although our study was not designed to evaluate the effect of duration of therapy on efficacy, we interpret these results favorably, as it has been previously shown that continuous therapy and longer durations of treatment are associated with improved patient outcomes, including better tolerability and longer survival.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The analysis did not consider patient attrition over time, possibly leading to an overestimate in adherence. 7 However, we show that duration of therapy for DARA-based regimens in the real-world is relatively long and adherence is high. Although our study was not designed to evaluate the effect of duration of therapy on efficacy, we interpret these results favorably, as it has been previously shown that continuous therapy and longer durations of treatment are associated with improved patient outcomes, including better tolerability and longer survival.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have evaluated real-world use of DARA in the United States and reported that the median duration of treatment across LOTs (with various combinations) was 9.8 months, 7 which is slightly longer compared with a median of 6.5 months reported by another group (with ranges from 4.1 to 8.8 months, depending on the LOT). 6 These studies do not follow DARA continuously.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…36 Estimated total cost of administering IV daratumumab over 52 weeks, with 23 expected infusions, is US $167,826. 37 For context, the mean cost of cyclophosphamide per 100mg infusion in 2023 US dollars is $17.942, for an estimated total cost per 6 regimen cycles at dosing 300mg/m 2 in the average 1.91m 2 individual of $1,291.82. 38 The mean cost of bortezomib per 0.1mg injection in 2023 US dollars is $2.289, for an estimated total cost per 6 regimen cycles at dosing 1.3mg/m 2 in the average 1.91m 2 individual of $1364.06.…”
Section: Daratumumab In Plasma Cell Dyscrasiasmentioning
confidence: 99%